Coronavirus disease 19 with gastrointestinal symptoms as initial manifestations: a case report - Wu, Chun-Yang; Yu, Xiao-Pin; Ma, Ada Hoi Yan; Wang, Li-Ping; Yang, Nai-Bin; Li, Guo-Xiang; Shi, Jie-Jun; Qian, Guo-Qing (2020)
Since the outbreak of coronavirus disease 2019 (COVID-19) in December 2019, an epidemic has spread rapidly worldwide. COVID-19 is caused by the highly infectious severe acute respiratory syndrome coronavirus-2. A 42-year-old woman presented to hospital who was suffering from epigastric discomfort and dyspepsia for the past 5 days. Before the onset of symptoms, she was healthy, and had no travel history to Wuhan or contact with laboratory-confirmed COVID-19 cases. An examination showed chronic superficial gastritis with erosion and esophagitis. Enhanced magnetic resonance imaging of the abdomen showed a lesion in the right lower lobe of the lungs. Chest computed tomography showed multiple ground-glass opacity in the lungs. Reverse transcription-polymerase chain reaction was negative for severe acute respiratory syndrome coronavirus-2. There was no improvement after antibiotic treatment. Polymerase chain reaction performed 2 days later was positive and she was diagnosed with COVID-19. After several days of antiviral and symptomatic treatments, her symptoms improved and she was discharged. None of the medical staff were infected. Clinical manifestations of COVID-19 are nonspecific, making differentiating it from other diseases difficult. This case shows the sequence in which symptoms developed in a patient with COVID-19 with gastrointestinal symptoms as initial manifestations.